Responsibilities of Media in Contemporary Asymmetric Conflicts (Kriminalističke teme, 2003)
In today’s asymmetric conflicts, a nation, movement or organization that is smaller in sense of armory prepares terrorist action counting on a creepy spectacularly of a terrorist act itself.Such, act grasps the attention of broad population and warns public on specific political aims of that organization.A boy “loaded” with explosive, who fuses it in a luxury restaurant, knows that at least for that day his act would be among main headlines in the press. TV station would begin their programs with that news. Other more complicated terrorist actions would be analyzed in media much longer.Simultaneously, a political leader of any terrorist organization tries to maximally use the strong impression that terrorist act left in the public. He would also try to manipulate media for their own use (like political leader of a country that uses conventional ways of their armed forces engagement).The responsibility of media tn reporting about this kind of violence, used for political purposes, proves to be important fact in protection of modern democratic society. Media with low professional standards can be very easily misused as part of such fight. On the other hand, serious media could be among the most important factors of preserving stability and peace tn a politically region.